In silico and In vivo Studies of Raja Banana Peel Extract as Anti-Obesity on Lipid Profile and Adipokines in Male Rats with Obesity - Devina, Kezia Elian; Larasati, Aurelia Alisa Putri; Pricela, Nanda Jhaneta; Prasetyo, Andika; Indarto, Dono; Susilawati, Tri Nugraha; Sulastomo, Heru (Trends in Sciences, 2025)
Banana peels contain nutrients and active compounds that have anti-obesity effects. Quercetin and flavonoids identified in banana peels have emerged as a promising candidate for developing novel therapeutics to address obesity. Quercetin can reduce fat accumulation by regulating lipogenesis. Research on in silico on banana peel extract and the effects of banana peel on lipid profiles and adipokine levels is still limited. This study aimed to analyze the effects of raja banana peel extract (RBPE) on lipid profiles, dipeptidyl peptidase-4 (DPP-4) specific activity, leptin, and adiponectin levels in male Wistar rats with obesity. Molecular docking was performed to demonstrate the interaction between quercetin and DPP-4, leptin, and adiponectin receptors in carbohydrate and fat regulation. An in vivo study used a pre-posttest control group design in 30 male Wistar rats with obesity. This study measured total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglyceride (TG), DPP-4 specific activity, leptin, and adiponectin levels. The results showed that the RBPE administration decreased significantly TC (p < 0.001) and LDL-C levels (p < 0.001), increased HDL-C level (p < 0.001), increased DPP-4 specific activity (p < 0.001), and reduced leptin levels, but did not increase adiponectin levels (p = 0.274). In conclusion, RBPE administration might offer a promising therapeutic approach for obesity by regulating cholesterol and lipid metabolism. HIGHLIGHTS Raja Banana Peel Extract (RBPE) contains quercetin, which has anti-obesity effects. Quercetin potentially interacts with DPP-4 protein, leptin, and adiponectin receptors. RBPE significantly lowers TC, LDL-C, and leptin levels. RBPE significantly increases HDL-C levels and DPP-4 specific activity. GRAPHICAL ABSTRACT